Photochemical determination of O densities in the Martian thermosphere: Effect of a revised rate coefficient. Issue 16 (16th August 2017) - Fox, Jane L.; Johnson, Austin S.; Ard, Shaun G.; Shuman, Nicholas S.; Viggiano, Albert A.
Abstract: We investigate the production and loss rates of O 2 + in the photochemical equilibrium region of the Martian ionosphere near the subsolar point. We adopt neutral and ion densities measured by the Mars Atmosphere and Volatiles EvolutioN (MAVEN) Neutral Gas and Ion Mass Spectrometer (NGIMS), electron densities and temperatures measured by the Langmuir Probe and Waves, and ion temperatures measured by the Supra‐Thermal and Thermal Ion Composition instruments on the MAVEN spacecraft. Contrary to the conventional wisdom, we find that loss of O 2 + by dissociative recombination is balanced mainly by production due to the reaction of O + with CO2, with a smaller contribution due to the reaction of CO 2 + with O. We find that the O densities derived from this calculation are larger than those measured by the NGIMS instrument by a factor that averages about 4 over the range of 130–155 km. This general conclusion is supported by a newly measured rate coefficient for the reaction of O with CO 2 +, which is smaller by a factor of about 6 than the only value in the literature, which was measured 47 years ago. Key Points: Photochemical equilibrium calculations of O 2 + show that the major source of O 2 + is the reaction of O+ with CO2, not CO 2 + with O on Mars The derived O densities are a factor of 3‐5 larger than the values measured by the NGIMS instrument on the MAVEN spacecraft A new rate coefficient for the reaction of O with CO 2 + is reported; this value is a factor of 6 smaller that the one measured 47 years ago